Technology for Sustainable Urban Food Ecosystems in the Developing World: Strengthening the Nexus of Food–Water–Energy–Nutrition - Davies, Fred T.; Garrett, Banning (Frontiers in Sustainable Food Systems, 2018)
Smart integration of technology can help create sustainable urban food ecosystems (UFEs) for the rapidly expanding urban population in the developing world. Technology, especially recent advances in digital-enabled devices based on internet connectivity, are essential for building UFEs at a time when food production is increasingly limited on a global scale by the availability of land, water, and energy. By 2050, two-thirds of the world will be urban—and most of the net world population growth will occur in urban regions in the developing world. A food crisis is looming, with the developing world ill-prepared to sustainably feed itself. We identify 12 innovative technology platforms to advance the UFEs of the developing world: (1) connectivity—information delivery and digital technology platforms; (2) uberized services; (3) precision agriculture (GPS, IoT—Internet of things, AI—artificial intelligence, sensing technology); (4) CEA—controlled environment agriculture, including vertical farms; (5) blockchain for greater transparency, food safety, and identification; (6) solar and wind power connected to microgrids; (7) high-quality, enhanced seeds for greater yield, nutrition, climate, and pest resistance; (8) advanced genetics, including gene editing, synthetic biology, and cloud biology; (9) biotechnology, including microbiome editing, soil biologicals, cultured meat, alternative proteins to meat and dairy; (10) nanotechnology and advanced materials; (11) 3-D printing/additive manufacturing; and (12) integration of new tech to scale-up underutilized, existing technologies. The new tech-enabled UFEs, linked to value-chains, will create entrepreneurial opportunities—and more efficiently use resources and people to connect the nexus of food, water, energy, and nutrition.